Navigating Indonesia's Digital Transformation: Exploring Entrepreneurial Opportunities in E-commerce and Fintech - Sitti Hikmawatty; Gustian Djuanda; Gina Sahadatun Nisa (Fakultas Ekonomi Universitas Garut, 2025)
This study looks into how initiatives for digital transformation, the expansion of the e-commerce industry, innovation, and the adoption of fintech affect entrepreneurial ventures in the fintech and e-commerce sectors, and how those ventures then affect the financial performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia. A survey-based quantitative analysis was carried out to gather information from 293 MSMEs operating in different regions and industry sectors throughout Indonesia. The Partial Least Squares (PLS) approach was used in Structural Equation Modeling (SEM) to assess the correlations between important variables. The findings show a strong positive correlation between fintech acceptance, innovation, e-commerce sector growth, entrepreneurial endeavors, and digital transformation projects. Additionally, it was discovered that entrepreneurial endeavors and economic performance were favorably correlated. These results highlight how important digital entrepreneurship is to Indonesia's economic development and innovation, especially in the MSME sector. Policymakers, industry stakeholders, and MSMEs looking to harness digital technology and encourage entrepreneurship to improve economic performance would find the study's insights to be highly beneficial.